The absolute and the restricted, and their meanings - Samsuri, Nur Bahiyah Adibah; Yaakob, Fathiah; Mat, Nur Insyira; Zabidi, Nur Ain Amalin; Wan Abdul Rahim, Wan Norsyazwanie; Mohd Rizal, Maisarah Izzah Hazwani (2024)
Slide Presentation: “The absolute and the restricted, and their meanings”